PENGARUH MODEL PROJECT BASED LEARNING BERBASIS DEEP LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS MATERI INDONESIAKU KAYA HAYATI KELAS V SDN CIGINTUNG - Salsabilla, Yuriska; marsha santoso, Yolanda; Sri Agung , Yuliati; Setiawati , Ina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning outcomes of students in Science and Social Learning (IPAS) subject in elementary schools is a problem that requires serious attention. This study aims to determine the effect of implementing the Deep Learning-Based Project Based Learning (PjBL) model on the learning outcomes of fifth grade students at SDN Cigintung in the IPAS subject on the topic of Indonesiaku Kaya Hayati. The study used a quantitative approach with a pre-experimental method and One Group Pretest-Posttest Design. The research subjects were all 19 fifth grade students at SDN Cigintung, determined through total sampling technique. Data collection instruments consisted of 20 multiple-choice learning outcome tests that had been tested for validity and reliability. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, and Wilcoxon Signed-Rank Test with a significance level of α = 0.05. The results showed a significant improvement in students’ learning outcomes, marked by an average pretest score of 49.11 which increased to 87.47 on the posttest. All students who were previously mostly in the low category successfully achieved the high category after the treatment. The Wilcoxon test produced a p-value = 0.000 < 0.05, indicating that there is a significant effect of implementing the Deep Learning-Based PjBL model on students’ learning outcomes. This study concludes that the Deep Learning-Based PjBL model is effective in improving students’ learning outcomes in the IPAS subject in elementary school.